Sleep-Induced Glottis Closure in Multiple System Atrophy Evaluated by Four-Dimensional Computed Tomography - Ueha, Rumi; Maeda, Eriko; Ino, Kenji; Shimizu, Takahiro; Sato, Taku; Goto, Takao; Yamasoba, Tatsuya (Frontiers in Medicine, 2020)
Multiple system atrophy (MSA) is a progressive neurodegenerative disorder. Since patients with MSA often have sleep-related respiratory disorders including upper-airway obstruction and/or central sleep disturbance, appropriate evaluation of the upper airway especially during sleep may be indispensable. Fiberoptic laryngoscopy during diazepam-induced sleep has been reported for upper-airway obstruction verification. However, some patients cannot endure the uncomfortable sensation of the fiberscope. To address these issues, we devised a protocol of four four-dimensional computed tomography (4D-CT) for upper-airway evaluation during sleep. Here, we report the case of patient with MSA who was evaluated for upper-airway obstruction during sleep using 4D-CT. A 46-year-old man (height 1.60 m, weight 79 kg) was admitted to our neurological department for tracheal intubation because of a sudden onset of respiratory failure occurring at night. At the age of 45 years, he was diagnosed as MSA with predominant parkinsonism. As pulmonary disease had been excluded and his swallowing was normal, our differential diagnoses were central sleep apnea or obstructive sleep apnea related to his MSA or obstructive sleep apnea (SA) related to his obesity. A tracheostomy was done to maintain the airway after extubation. Polysomnography showed obstructive SA and not central SA. Awake fiberoptic laryngoscopy showed no upper airway obstruction but bilateral vocal abduction impairment (BVAI) during inspiration. To assess the spatial and temporal conditions of the upper respiratory tract—the patient could not tolerate sleep laryngoscopy—we carried out a 4D-CT. Reconstructed 4D-CT images of respiration during sleep showed clear abnormalities: glottis closure at the terminal stage of inspiration and subsequent velopharyngeal closure. As glottis closure does not occur normally in obesity patients, the cause of the respiratory failure in this patient was considered MSA-related sleep-induced airway obstruction. We decided to keep the tracheostoma, because BVAI in patients with MSA may be getting worse, although central apnea after tracheostomy may cause sudden central origin-related death; 4 months postoperatively, the patient had experienced no further airway-related complications. This report indicates that 4D-CT sequential upper-airway assessment during sleep is useful for determining the abnormalities causing obstructive SA in patients with MSA.